USING A GIS-MCDM APPROACH TO WIND AND SOLAR SITE SELECTION IN TUNISIA - Wedyan. G. nassif,; Dalila Elhmaidi,; Yaseen K. Al-Timimi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate a comprehensive methodology and its ensuing results for identifying potential sites for wind power plants (WPPs) and solar photovoltaic plants (SPVPs) across Tunisia, a crucial step given the significant long-term investment these plants entail. Using Geographic Information Systems (GIS) integrated with Multi-Criteria Decision-Making (MCDM) and underpinned by the Analytical Hierarchy Process (AHP), this research meticulously weighs and maps various site-specific criteria essential for site suitability assessment. The results indicate that approximately 1183 km² (1.8% of Tunisia's total area) and 2533 km² (3.7%) are optimally suited for large-scale SPVPs and WPPs, respectively. the prime locations for wind energy are predominantly in the northwest, southwest, southeast, and parts of the north, while the central and southern regions harbor the most potential for solar energy development due to favorable solar irradiance.